Nursing care for a hospitalised infant with Edwards’ syndrome – case study - Chmielewska, Alicja; Łozińska-Czerniak, Anna (Medycyna Paliatywna/Palliative Medicine, 2024)
This study aims to present the care provided by medical staff for a newborn with Edwards’ syndrome. The study analyses palliative care for a newborn diagnosed with a lethal defect, considering the ethical aspects and the holistic extent of the issue. It highlights aspects related to parental psychological disorders, as well as possibilities for further therapy. The paper presents the position regarding healthcare staff training in palliative care and access to psychological assistance for this professional group.